THE ROLE OF INTEGRATED ISLAMIC COMMERCIAL AND SOCIAL FINANCE IN REDUCING INCOME INEQUALITY IN INDONESIA - Widodo, Arif (Journal of Islamic Monetary Economics and Finance, 2019)
Recent years saw the heated debates among prominent economists on the growinginequality in advanced economies, and accordingly, many solutions to this seriousproblem have been put forward. Among the practical-cum-workable solution isprogressive taxation for wealth and income, especially the top one percent. Such asolution, however, has been implemented in Islamic perspective what so-called,zakah which is now referred to as social finance. In this paper, using the Gini coefficient datacovering 34 provinces in Indonesia over a decade, we examine whether the role ofsocial finance in tandem with commercial finance can adequately solve the problemof wealth distribution in Indonesia, one of the largest Democratic-Muslim countriesin the world. Using the Generalized Method of Moments (GMM) model, the resultsdemonstrated that Islamic commercial finance solely is proven statistically incapable oftackling inequality while the social finance (zakah) is performing very well in this matterover all specifications. Most importantly, when both are incorporated in a model, theresult showed a significant reduction in income inequality implying that the integratedIslamic finance which can be implemented in both Islamic microfinance institution andIslamic banking is more capable, as opposed to when both are separated, of helpingaddress the income inequality problem in Indonesia.